Oscillation of Nonlinear First Order Neutral Differential Equations - Baghdad Science Journal (مجلة بغداد للعلوم, 2007)
In this paper, the author established some new integral conditions for the oscillation of all solutions of nonlinear first order neutral delay differential equations. Examples are inserted to illustrate the results.